Inhibition of the lysophosphatidylinositol transporter abcc1 reduces prostate cancer cell growth and sensitizes to chemotherapy - Emmanouilidi, Aikaterini; Casari, Ilaria; Akkaya, B.G.; Maffucci, T.; Furic, L.; Guffanti, F.; Broggini, M.; Chen, X.; Maxuitenko, Y.Y.; Keeton, A.B.; Piazza, G.A.; Linton, K.J.; et al. (2020)
Expression of ATP-binding cassette (ABC) transporters has long been implicated in cancer chemotherapy resistance. Increased expression of the ABCC subfamily transporters has been reported in prostate cancer, especially in androgen-resistant cases. ABCC transporters are known to efflux drugs but, recently, we have demonstrated that they can also have a more direct role in cancer progression. The pharmacological potential of targeting ABCC1, however, remained to be assessed. In this study, we investigated whether the blockade of ABCC1 affects prostate cancer cell proliferation using both in vitro and in vivo models. Our data demonstrate that pharmacological inhibition of ABCC1 reduced prostate cancer cell growth in vitro and potentiated the effects of Docetaxel in vitro and in mouse models of prostate cancer in vivo. Collectively, these data identify ABCC1 as a novel and promising target in prostate cancer therapy.